PENETAPAN PENAHANAN TERHADAP TERSANGKA DALAM DUGAAN KASUS PEMBUNUHAN BERENCANA - Safitri Mashuda Nurul; Abraham Ferry Rosando (Gapenas Publisher, 2023)
Murder cases are abhorrent to basic human decency; Murder is defined in Article 338 of the Criminal Code and there are three different types of murder, namely firstly by accident and by mistake, secondly by intentional killing but with tools that are not meant to kill or to be toyed with and thirdly murders that are planned and carried out with the intent to kill. In accordance with Article 340 of the Criminal Code, premeditated murder is murder in which the method used to commit the murder, the time it was committed, or the method used to cover up the crime was intentional and planned. Two parts, or factors, make up the subjective and objective nature of premeditated murder. This is why the punishment is harsher than ordinary murder. As stipulated in the Criminal Procedure Code, a suspect or defendant has the right to be accompanied by a legal adviser during the entire interrogation process. Individual freedom of movement was severely restricted and eventually revoked during detention. Because the writer cannot ensure the integrity of the justice system here, the writer will use a normative juridical law study that takes a statutory and conceptual approach. Investigators, public prosecutors and judges must exercise due diligence and moral prudence within the limits of such arrest and/or detention